Application of case teaching technique in educational process - Tvaronavičiene, Manuela; Ginevičius, Romualdas (Journal of Business Economics and Management, 2003)
In the article a case study method, which is amply used at Harvard Business School in United State of America and also at European Business Schools characterized by top ratings, has been analyzed. A case study method, as teaching tool of business management students and executives, accomplishes and enriches conventional methods of teaching, such as lecturing, assigning of practical tasks, reading of specialty literature etc. Nevertheless, despite popularity of a case study method among prestigious Business Schools, various approaches to definition of a proper for teaching process case could be found, also different emphasizes on process of application of this teaching method have been put. The article deals with following issues: at first, characteristic features of case making it proper for teaching purposes have been considered; the second, detailed a case analysis’ methodic, which enabled to increase efficiency of teaching process of business management in universities, has been presented. The methodic has been drawn up having objective more expressed orientation of teaching process to application of theoretical frameworks to solving real issues in specific business situations and development of concrete business decisions and also to form skills how to predict and evaluate plausible outcomes of alternative decisions. Practical application of a case study method let to accelerate acquisition of practical skills of students and make them better prepared for searching successful business decisions. First Published Online: 14 Oct 2010